Differential phosphorylation of the N‐terminal extension regulates phytochrome B signaling. Issue 4 (7th November 2019) - Viczián, András; Ádám, Éva; Staudt, Anne‐Marie; Lambert, Dorothee; Klement, Eva; Romero Montepaone, Sofia; Hiltbrunner, Andreas; Casal, Jorge; Schäfer, Eberhard; Nagy, Ferenc; Klose, Cornelia
Summary: Phytochrome B (phyB) is an excellent light quality and quantity sensor that can detect subtle changes in the light environment. The relative amounts of the biologically active photoreceptor (phyB Pfr) are determined by the light conditions and light independent thermal relaxation of Pfr into the inactive phyB Pr, termed thermal reversion. Little is known about the regulation of thermal reversion and how it affects plants' light sensitivity. In this study we identified several serine/threonine residues on the N‐terminal extension (NTE) of Arabidopsis thaliana phyB that are differentially phosphorylated in response to light and temperature, and examined transgenic plants expressing nonphosphorylatable and phosphomimic phyB mutants. The NTE of phyB is essential for thermal stability of the Pfr form, and phosphorylation of S86 particularly enhances the thermal reversion rate of the phyB Pfr–Pr heterodimer in vivo . We demonstrate that S86 phosphorylation is especially critical for phyB signaling compared with phosphorylation of the more N‐terminal residues. Interestingly, S86 phosphorylation is reduced in light, paralleled by a progressive Pfr stabilization under prolonged irradiation. By investigating other phytochromes (phyD and phyE) we provide evidence that acceleration of thermal reversion by phosphorylation represents a general mechanism for attenuating phytochrome signaling.